Human factors testing and evaluation - Meister, David, 1924- (Advances in human factors/ergonomics, 1986)
Human factors measurement has characteristics that set it apart from psychological or engineering measurement and for that reason, human factors testing and evaluation deserves special treatment. The many excellent texts available in the behavioral area do not give an adequate picture of this topic, and this is particularly unfortunate because testing and evaluation (T & E) is an integral part of human-machine system design and operation. The emphasis in this book is on why and how to conduct such testing. One of its outstanding features is its pragmatism; based on his past experience in system testing, the author recognizes the difficulties that occur in testing and indicates how these may be overcome or minimized. Special attention has been paid to the context in which T & E is conducted. Although the book contains detailed procedures for performing T & E, the logic and the conceptual foundation of testing have not been overlooked. Comparisons are made with laboratory-centered experimentation. For those with research interests, the author points out the many research questions that can be answered by system testing. An illustrative case history of a T & E program for a fictional system has been included to provide ``real life'' context. Special problem areas in T & E are emphasized, in particular human error data collection, the evaluation of computerized systems and software, the measurement of maintenance technician and team performance; workload and training effectiveness testing. Special attention is also paid to environmental testing (e.g. temperature, lighting, noise, vibration, etc.). One chapter reviews all the relevant T & E literature including government documents that may not be readily available to the general reader. As part of the preparation for writing this text a survey was made of 45 distinguished T & E specialists in order to determine their characteristic T & E practices.